DESCRIPTION OF CREATIVE THINKING SKILLS BASED ON CREATIVE THINKING TEST IN OPTICAL MATERIALS - Napitupulu, Jeremia Andi Sahputra; Bunawan, Wawan (UNIVERSITAS NEGERI MEDAN, 2023)
This study aims to describe the creative thinking of high school students in solving physics problems. Creative thinking skills are crucial for developing long-term success and improving the quality of life. This research is qualitative descriptive research, research methods used in research is a qualitative method, participants in this study were students of class XI SMA IPA 2 and IPA 6, totaling 66 students, data obtained from student's thinking creativity test instrument which is strengthened by data from student and teacher interviews. Data analysis referred to three indicators of creativity used in the study: fluency, flexibility, and originality. The results showed that the aspect of fluency exhibits the highest average proportion among the characteristics of creative thinking, while the aspect of originality shows the lowest average proportion. It is necessary to apply various kinds of learning models that are applied to be able to improve students' creative thinking skills. Although there are some students with lower levels of creative thinking, it does not imply that they lack creativity, as creativity can be fostered through other activities.